Cardiac responses to transrectal examination of lactating and non-lactating dairy cows - Kézér, Fruzsina Luca; Kovács, Levente; Jurkovich, Viktor; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
In this study we evaluated heart rate (HR) and parasympathetic parameters of heart rate variability (HRV) to monitor cardiac stress responses to palpation per rectum in lactating (n = 11) and non-lactating (n = 12) dairy cows. HR and HRV were measured from 40 min before the examination until 120 min after it was done. HR, the root mean square of successive differences (RMSSD) and the high frequency component (HF) of HRV were analyzed in equal length of 5 min data segments. To compare cardiac responses to palpation per rectum between groups, changes in HR and HRV parameters were calculated as area under the curve (AUC). Although an immediate increase was found in HR during the examination in both lactating (+21.4 ± 2.4 beats/min) and non-lactating animals (+20.6 ± 2.3 beats/min), no differences were detected between groups using by the AUC method. The rise of HR in both groups along with a parallel decline of RMSSD (lactating cows: –5.2 ± 0.4 ms, non-lactating cows: –5.1 ± 0.4 ms) and HF (lactating cows: –10.1 ± 0.8 nu, non-lactating cows: –16.9 ± 1.2 nu) during transrectal palpation reflected to an increase in the sympathetic, and a decrease in the vagal tone. The amplitude and the maximum RMSSD and HF values were higher in non-lactating cows than in lactating animals suggesting a higher short-term cardiac responsiveness of non-lactating ones. However, the magnitude and the duration of the stress response were greater in lactating cows, as indicated by the analysis of AUC. Cows’ response to stress experienced during and after palpation per rectum was more prominent in vagal indices of HRV than in HR. Based on our results, the impact of transrectal examination on the cows’ cardiac stress responses may have an impact on animal welfare on dairy farms. Further research is required to find out whether the differences due to lactation are physiological or management-related.
Keywords: heart rate; heart rate variability; palpation per rectum; pain; dairy cow